EVALUATION OF THE IMPLEMENTATION OF THE CHILD-FRIENDLY SCHOOL PROGRAM AT KLENDER 13 STATE ELEMENTARY SCHOOL, EAST JAKARTA - HANDAYANI, Exabella (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
Klender 13 State Elementary School, East Jakarta is one of the schools carrying out an evaluation of the implementation of Child Friendly Schools (SRA) to realize children's rights to good and quality education. This research aims to evaluate program implementation, strategies and the impact of implementing SRA at the Klender 13 State Elementary School, East Jakarta. This research uses a descriptive qualitative approach. The data collection techniques were obtained through observation, interviews and documentation studies. Next, the collected data was analyzed using the CIPP evaluation model analysis model which includes procedures for data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation. This research found the following results: (1) The SRA program at SDN Klender 13 was implemented by integrating all existing school policies, school programs and school activities. (2) The strategy for implementing the SRA program at SDN Klender 13 includes forming an SRA program implementation team, fulfilling SRA component indicators, carrying out monitoring and evaluation, and being responsive to the results of monitoring and evaluation of SRA program implementation. (3) The implementation of SRA has had an impact on SDN Klender 13 which includes changes in student character, increased student achievement both academic and non-academic, students feel more calm and comfortable physically and emotionally at school, there is an increase in teacher achievement and skills, communication is established and positive collaboration between teachers and parents, increasing madrasah achievements, and making the madrasah's reputation better known in the community.